The Mechanism of Non-Photochemical Quenching in Plants: Localization and Driving Forces. (30th December 2020) - Ruban, Alexander V; Wilson, Sam
Abstract: Non-photochemical chlorophyll fluorescence quenching (NPQ) remains one of the most studied topics of the 21st century in photosynthesis research. Over the past 30 years, profound knowledge has been obtained on the molecular mechanism of NPQ in higher plants. First, the largely overlooked significance of NPQ in protecting the reaction center of photosystem II (RCII) against damage, and the ways to assess its effectiveness are highlighted. Then, the key in vivo signals that can monitor the life of the major NPQ component, qE, are presented. Finally, recent knowledge on the site of qE and the possible molecular events that transmit ΔpH into the conformational change in the major LHCII [the major trimeric light harvesting complex of photosystem II (PSII)] antenna complex are discussed. Recently, number of reports on Arabidopsis mutants lacking various antenna components of PSII confirmed that the in vivo site of qE rests within the major trimeric LHCII complex. Experiments on biochemistry, spectroscopy, microscopy and molecular modeling suggest an interplay between thylakoid membrane geometry and the dynamics of LHCII, the PsbS (PSII subunit S) protein and thylakoid lipids. The molecular basis for the qE-related conformational change in the thylakoid membrane, including the possible onset of a hydrophobic mismatch between LHCII and lipids, potentiated by PsbS protein, begins to unfold.